Innovation in Communication Models for Women’s Economic Empowerment through Business Incubators: A Case Study of the PADU Program at Universitas Subang - Nur’aeni Nur’aeni; Ine Anggraini; Adhie Surachman; Slamet Wahyudi Yulianto (CV. Syntax Corporation Indonesia, 2026)
This study aims to examine the empowerment communication model implemented in the PADU (Perempuan Andalan dalam Dunia Usaha Women Champions in Business) business incubator program at Universitas Subang as a means to enhance entrepreneurial capacity among female students. Using a mixed-method approach, this research combined quantitative data collected through questionnaires (50 respondents) and qualitative data obtained through in-depth interviews, participatory observation, and document analysis. The findings from 50 respondents indicate significant improvements in financial literacy (80%), digital marketing skills (70%), self-confidence (90%), and the ability to create business prototypes (70%). However, challenges remain regarding business sustainability after the incubation process and participants’ independence. Based on interview results, the communication model employed in the program is participatory, transformative, and contextual. Participatory communication encourages active involvement from participants; transformative communication helps shift their mindset from consumers to entrepreneurs; and contextual communication ensures that the materials delivered are relevant to Subang’s local potential. This research emphasizes that communication innovation within university-based business incubators is not merely aimed at transferring technical skills but also at fostering critical awareness, entrepreneurial identity, and supporting the achievement of the Sustainable Development Goals (SDGs), particularly gender equality (SDG 5) and inclusive economic growth (SDG 8).